Risk Factor of Low-Birth-Weight Baby Prevalence at Fakfak Public Hospital West Papua - Amelia, Dian Rizky; Situmorang, Lasmauli (UNUSA Press, 2022)
Background: The high number of infant mortality rate in Indonesia relate to Low Birth Weight (LBW) babies that be a problem of public health sector. LBW babies are facing several health problems such as various diseases that arise in the first six days of life, and can experience long-term problems such as impaired development and growth. This is inseparable from the mother's risk factors during pregnancy. West Papua Province contributes 23.8% of LBW cases in Indonesia. Fakfak District Hospital as the only referral hospital in West Papua Fakfak district still has many problems related to cases of low birth weight babies. Objective: To know the risk factors of LBW prevalence based on maternal age, gestational age, parity, hemoglobin levels, premature rupture of membranes (PROM), and preeclampsia in Fakfak public hospital, West Papua. Methods: This study is an observational analytic with cross sectional study in Fakfak public hospital during April 2021 till October 2021. Purposive sampling method used to obtain the samples from medical records that fit to inclusion and exclusion criteria (N=418). Data was analyzed with SPSS statistic for Mac used Chi-square test and logistic regression method. The significant level of the test was p < 0,05. Results: A total of 418 newborn were included during study period. There were significant results in gestasional age (p=0,000) (OR 7,23, CI95% 1,13-10,4), premature rupture of membranes (PROM) p=0,000 (p<0,05) OR 14,23 (CI95% 7,7-26,2), hemoglobin levels (p=0,000) (OR 3,47 CI95% 1,99-6,03), preeclampsia (p=0,000) (OR 9,76 CI95% 5,39-17,6). The regression test showed significant result at four variables. Conclusion: Gestational age, PROM, hemoglobin levels, and preeclampsia are risk factors that significant lead to LBW prevalence in Fakfak public hospital, West Papua.